Response surface methodology routed optimization of performance of hydroxy gas enriched diesel fuel in compression ignition engines - Usman M.; Nomanbhay S.; Ong M.Y.; Saleem M.W.; Irshad M.; Hassan Z.U.; Riaz F.; Shah M.H.; Qyyum M.A.; Lee M.; Show P.L. (MDPI AG, 2023)
In this study, the response surface methodology (RSM) optimization technique was em-ployed for investigating the impact of hydroxy gas (HHO) enriched diesel on performance, acoustics, smoke and exhaust gas emissions of the compression ignition (CI) engine. The engine was operated within the HHO flow rate range of 010 L/min and engine loads of 15%, 30%, 45%, 60% and 75%. The results disclosed that HHO concentration and engine load had a substantial influence on the response variables. Analysis of variance (ANOVA) results of developed quadratic models indicated the appropriate fit for all models. Moreover, the optimization of the user-defined historical design of an experiment identified an optimum HHO flow rate of 8 L/min and 41% engine load, with composite desirability of 0.733. The responses corresponding to optimal study factors were 25.44%, 0.315 kg/kWh, 117.73 ppm, 140.87 ppm, 99.37 dB, and 1.97% for brake thermal efficiency (BTE), brake specific fuel consumption (BSFC), CO, HC, noise, and smoke, respectively. The absolute percentage errors (APEs) of RSM were predicted and experimental results were below 5%, which vouched for the reliable use of RSM for the prediction and optimization of acoustics and smoke and exhaust emission characteristics along with the performance of a CI engine. 2021 by the authors. Licensee MDPI, Basel, Switzerland.